Pengaruh Terpaan Iklan Akun Instagram @deliciousbali Terhadap Niat Membeli Produk Kuliner di Bali - Sekaringtyas, Yusma Ayu; Pradipta, Ade Devia; Alit Suryawati, I Gusti Agung (E-Jurnal Medium, 2020)
ABSTRACT @Deliciousbali is one of the most-followed Instagram accounts number 1 in Bali which provides Balinese culinary recommendations which has reached 298.000 followers in 2020. This account is not only being used to give some culinary recommendations, but also being used as such a  new marketing communications platform to publicy both foods and beverages in Bali with Instagram as its support. In this research, kind of method that has been used is quantitative explanatory with Uses and Effects theory and Hierarcy of Effects Model. This research shows that media exposure in advertising of @deliciousbali has impacted on someone’s purchase intentions with total score of correlation 0,781 given to the right point that these variables are strongly correlated  resulting at 60,9 % level of impact.  Moreover,  the intensity of media exposure and purchase intention are not affected by gender which is shown at its comparison between both variables are nearly the same. Keyword: Instagram, Purchase Intentions, Advertisement Exposure, Uses and Effects.